Health as a Family Matter : Do Intra-household Education Externalities Matter for Maternal and Child Health? - Lindelow, Magnus (2012)
This paper is concerned with the role of education as a determinant of health care choices. The central premise of the paper is that utilisation of health services is determined not solely by an individual's own education, but rather by a notion of effective education, which incorporates the educational attainment of other household members. The paper sets out a general framework for representing intra-household education externalities, and proposes a number of specific hypotheses concerning the way in which the education of different household members affects health care choices. These hypotheses are tested on data from Mozambique, focusing on maternity services, child immunisations, and child malnutrition. We draw four major conclusions from the analysis. First, while maternal education seems to be the education variable of primary importance for the health service and malnutrition variables under consideration, the education of other household members does have a significant and sometimes large effect. This is true not only for the spouse, but also the education of other individuals residing in the household. Second, the analysis suggests that while the education of the person (non-spouse) in the household with the highest level of education is important, the level of education of additional household members does not, as a rule, affect the use of services or child health outcomes. Third, the data provide no evidence of a gender difference in education externalities. Fourth, we examine the merits of two alternative representations of the education externality, but are unable to conclude unambiguously in favour of one specification over the other.